2012
DOI: 10.4103/0975-9476.96525
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a herbal extract gel in the treatment of gingivitis: A clinical study

Abstract: Background:Chronic gingivitis is the most prevalent in all dentate animals. Regular methods for controlling it have been found to be ineffective, which have paved the way for the use of herbal products as an adjunctive to mechanical therapy as they are free to untoward effects and hence can be used for a long period of time.Objective:The antigingivitis effect of a gel containing pomegranate extract was evaluated using a 21-day trial in patients with chronic gingivitis.Materials and Methods:Forty patients parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 11 publications
1
34
0
1
Order By: Relevance
“…There is an incentive to use alternative plant-based preparations as an adjunctive to mechanical therapy in the prevention and treatment of gingivitis, due to the health risks imposed by long-term use of chemical and pharmaceutical preparations and the lack of available dental care in lesser-developed countries. Results of a randomized clinical study of 40 patients with chronic gingivitis showed that significant improvements were obtained in the group that used a pomegranate extract gel along with mechanical debridement for 7 days when compared with patients using only control gel or mechanical debridement for the 7-day test period [45]. Another placebocontrolled human clinical trial of 32 young adults examined salivary measures relevant to oral health and gingivitis after using a pomegranate extract mouth rinse three times per day for 4 weeks or a placebo rinse [46].…”
Section: Clinical Studies On Gingivitismentioning
confidence: 99%
“…There is an incentive to use alternative plant-based preparations as an adjunctive to mechanical therapy in the prevention and treatment of gingivitis, due to the health risks imposed by long-term use of chemical and pharmaceutical preparations and the lack of available dental care in lesser-developed countries. Results of a randomized clinical study of 40 patients with chronic gingivitis showed that significant improvements were obtained in the group that used a pomegranate extract gel along with mechanical debridement for 7 days when compared with patients using only control gel or mechanical debridement for the 7-day test period [45]. Another placebocontrolled human clinical trial of 32 young adults examined salivary measures relevant to oral health and gingivitis after using a pomegranate extract mouth rinse three times per day for 4 weeks or a placebo rinse [46].…”
Section: Clinical Studies On Gingivitismentioning
confidence: 99%
“…29 It is also reported that it can be beneficial in oral diseases like periodontitis [30][31][32] and gingivitis. 33 The present study assessed the activity of guava, particularly against putative periodontal pathogens. Collectively, the putative periodontal pathogens tested were A. actinomycetemcomitans and P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pomegranate extract results had been comparable to that of the chlorhexidine rinse. 47 …”
Section: Clinical Study On Combating Dental Plaquementioning
confidence: 99%